If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5u + 3)(9 + -1u) = 0 Reorder the terms: (3 + 5u)(9 + -1u) = 0 Multiply (3 + 5u) * (9 + -1u) (3(9 + -1u) + 5u * (9 + -1u)) = 0 ((9 * 3 + -1u * 3) + 5u * (9 + -1u)) = 0 ((27 + -3u) + 5u * (9 + -1u)) = 0 (27 + -3u + (9 * 5u + -1u * 5u)) = 0 (27 + -3u + (45u + -5u2)) = 0 Combine like terms: -3u + 45u = 42u (27 + 42u + -5u2) = 0 Solving 27 + 42u + -5u2 = 0 Solving for variable 'u'. Factor a trinomial. (9 + -1u)(3 + 5u) = 0Subproblem 1
Set the factor '(9 + -1u)' equal to zero and attempt to solve: Simplifying 9 + -1u = 0 Solving 9 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1u = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1u = 0 + -9 -1u = 0 + -9 Combine like terms: 0 + -9 = -9 -1u = -9 Divide each side by '-1'. u = 9 Simplifying u = 9Subproblem 2
Set the factor '(3 + 5u)' equal to zero and attempt to solve: Simplifying 3 + 5u = 0 Solving 3 + 5u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5u = 0 + -3 5u = 0 + -3 Combine like terms: 0 + -3 = -3 5u = -3 Divide each side by '5'. u = -0.6 Simplifying u = -0.6Solution
u = {9, -0.6}
| (1.4)=3w | | 15n/85=385 | | 4/x-3=-2/3 | | 24-4k=-12k | | 20x-8-18x+3=15x-3-13x+14 | | 58.4-2.6=x | | 385=15n/85 | | X-4/3=x-4/2 | | 10a+3b+.5c=100 | | 2x-6=5x-14 | | 9x+5+x=-5x+35 | | x-8pi=3.14 | | 6xy=3x+4 | | y=(1+5x)/(9-7x) | | -6t=14+t | | 7x+3x-2=30 | | 5t+16=6-t | | 4(2x+5)=12 | | 7(x+y)=z | | 6(x+2/3) | | 21=3p-5 | | 2x/5+4/5=12/5 | | .25a=10 | | 2x^3-4x^2-10x+12=0 | | 8x+6=x+2 | | 5x-3+4=14 | | 2x^3-4x^2-10x+12=3 | | 14x=2x+6 | | 8g+10=3g | | Y-7-3y=10-6y*4 | | 4x-1=-27 | | 2b+4-5-b=-7 |